DEVELOPING ELT MATERIALS FOR YOUNG LEARNERS OF FOREIGN ENGLISH LANGUAGE LEARNERS - Clarry Sada (STKIP Melawi, 2014)
Abstrak: Bagian yang terpenting dalam persiapan mengajar adalah menentukan dan menyiapkan bahan ajar. Pada tahap ini, seorang guru harus dapat menyiapkan bahan yang sesuai bagi muridnya. Walaupun ada banyak jenis bahan ajar yang ditulis oleh para ahli, guru harus dapat menyesuaikan dengan material si guru dan juga dengan level dari pada murid. Jika material tidak relevan, maka akan berpengaruh pada pencapaian murid yang rendah atau pun buruk. Lebih dari itu, murid akan kurang berpatisipasi, cenderung merasa bosan, tidak komunikatif dan prosess pembelajaran menjadi tidak menarik. Oleh sebab itu, membuat atau pun memilih material yang sesuai adalah salah satu kunci kesuksesan dalam proses belajar mengajar. Dalam artikel ini, penulis bermaksud untuk mempresentasikan ide dalam membangun material ELT untuk murid yang berusia muda, yang akan difokuskan dalam situasi di Indonesia, dimana English Language Teaching (ELT) adalah bahasa asing. Dalam konteks ini, murid berusia muda adalah murid dengan usia di antara 6 tahun sampai 13 atau 14 tahun. Dengan demikian, murid berusia muda bisa saja murid pada level sekolah dasar sampai pada level sekolah menengah pertama. Artikel ini akan berfokus pada pengalaman penulis dan tentunya didukung oleh teori para ahli.Kata Kunci: kompetensi bahasa, membuat material ELTAbstract: A crucial part of teaching preparation is determining and preparing teaching materials. At this stage, a teacher should be able to provide a suitable and appropriate materials for his/her learners. Though there are varieties of teaching materials written by experts, the teacher should be able to just them accurately in order the materials are really appropriate and match with the learners level of language competence. If the materials are not relevant, the impact or result of teaching might be the learners achievement is low or poor. Moreover, the results could be in the form of poor participation of the learners, students feel boring, not communicative and uninteresting situation of teaching learning process. Therefore, developing or selecting an appropriate materials is one of the keys to successful teaching learning process. Thus, in this article, the writer intends to present some ideas of developing ELT matrials for young learners, which will focus on the situation in Indonesia, where English language teaching (ELT) as a foreign language. The young learners, in this context, are learners whose ages between 6 years old till thirteen or fourteen year old. Therefore, they may be learners at elementary level till junior secondary level. The discussion will be focused on the writers experiences and, of course, some theories proposed by the experts. Key Words: language competence, developing ELT matrials